New Constraints on the Young Lava Flow Profile in the Northern Mare Imbrium. Issue 16 (21st August 2020) - Yuan, Yuefeng; Wang, Fenghua; Zhu, Peimin; Xiao, Long; Zhao, Na
Abstract: Previous studies showed that the Eratosthenian mare (Em) unit in the northern Mare Imbrium, which is the location of the Chang'e‐3 (CE3) landing site, was simply formed by one period of thick lava flow. However, the CE3 Yutu rover equipped with lunar penetrating radar (LPR) recognized multilayered Em basalts based on the Channel 1 data reprocessed in this paper, indicating that three subdivided thin Eratosthenian lava flows should exist. The spatial variation and thickness distribution of each layer are further estimated based on the location of interfaces recognized from the shallow radar profile. Finally, we build a three‐dimensional stratigraphic model of young mare basalts with filling directions beneath the Chang'e‐3 landing site. The result infers that these young lava flows in the northern Mare Imbrium probably erupted intermittently from the same source. Plain Language Summary: The Chang'e‐3 spacecraft, which landed on the northern Mare Imbrium on the near side of the Moon, was equipped with lunar penetrating radar (LPR) on the Yutu rover and detected subsurface structures around the landing site. The structure of the regolith and those underneath young periods (Eratosthenian) and old periods (Imbrian) of lava flow layers have been constrained. However, due to data quality limitations, further information about the young period lava materials that exist pervasively in the northern Mare Imbrium is still lacking. This paper reprocessed the shallow part of LPR Channel 1 data and then ascertained multilayered young mare basalts underlying the regolith, which are interpreted as three periods of thin Eratosthenian lava flows. The filling directions beneath the CE3 landing site were also constrained based on the spatial distribution of interfaces recognized from LPR data. Key Points: Multilayered shallow structures are recognized beneath the Chang'e 3 landing site based on lunar penetrating radar Channel 1 data Three periods of Eratosthenian lava flows produced intermittent flooding in the northern Mare Imbrium A three‐dimensional stratigraphic model of young mare basalts is constructed in the area